Erythema Multiforme as a Complication in a Woman With Herpes Zoster - Agnes Stephanie Tanuwijaya; Niken Kusumaningrum; Hari Darmawan (Universitas Malahayati, 2026)
ABSTRACT Globally, the incidence of erythema multiforme (EM) is estimated to be between 0.01 and 1%, with a frequency of approximately 1.2 to 6 cases per million people per year. This condition can be triggered by viral infections, one of which is the varicella-zoster virus (VZV). Herpes zoster occurs due to reactivation of VZV and can cause EM. This condition requires special attention due to its potential severity and diagnostic difficulties. This case presentation describes this rare occurrence in a 43-year-old woman, exploring the clinical presentation, diagnostic approach, and therapeutic management of this unusual combination of virus-induced dermatological manifestations. The patient was given a combination of systemic corticosteroids and antivirals, as well as antibiotics and medications for other symptomatic symptoms. After a three-day hospital stay that showed clinical improvement, the patient was discharged with continued outpatient follow-up and a process to continue the prescribed oral and topical treatment with an appropriate reduction in the systemic corticosteroid dose. Keywords: Erythema Multiforme, Herpes Zoster, Herpes Zoster-Associated Erythema Multiforme (HAEM), Corticosteroid, Antiviral.